Teaching, Research and Academic Careers An Analysis of the Interrelations and Impacts - Checchi, Daniele; Jappelli, Tullio; Uricchio, Antonio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This open access book evaluates research quality, quality of teaching and the relationship between the two through sound statistical methods, and in a comparative perspective with other European countries. In so doing, it covers an increasingly important topic for universities that affects university funding. It discusses whether university evaluation should be limited to a single factor or consider multiple dimensions of research, since academic careers, teaching and awarding degrees are intertwined. The chapters included in the book evaluate teaching and research, also taking the gender dimension into account, in order to understand where and when gender discrimination occurs in assessment. Divided into five sections, the book analyses the administrative data on the determinants of career completion of university students; increasing precariousness of academic careers, especially of young researchers; methods designed to assess research productivity when co-authorshipand team production are becoming the standard practice; and interrelations between students$1 (Bachievements and teachers$1 (Bcareers driven by research assessment. It brings together contributions from a large group of economists, statisticians and social scientists working under a project sponsored by ANVUR, the Italian agency for the evaluation of teaching and research of academic institutions. From an international perspective, the findings in this book are particularly interesting because despite low tuition costs, tertiary education in Italy has relatively low enrolment rates and even lower completion rates compared to those in other European and American countries. This book is of interest to researchers of the sociology of education, education policy, public administration, economics and statistics of education, and to administrators and policy makers working in the area of higher education. .s
Introduction and general framework -- Introduction -- University assessment as governance device -- Teaching and students$1 (Bcareers in Italy -- Do family economic conditions influence play a role in university dropout? New evidence from administrative data -- Drop-out decisions in a cohort of Italian university students -- Recruiting and academic careers -- From PhD to Assistant Professor: analysis of recent cohorts -- Academic Careers and Fertility Decisions -- Conformism in research -- Social Network tools for the evaluation of individual and group scientific performance -- Topic-Driven Detection and Analysis of Scholarly Data. The Maverick Project -- Research quality and impact on teaching -- The relationship between teaching and research: the role of the institutional context and environmental factors -- Degree-level determinants of university student performance -- Teaching Efficiency of the Italian Universities: a Conditional Frontier Analysis.s
Keywords: Educational sociology; Educational tests and measurements; Education, Higher; Education -- Economic aspects; Education and state; Sociology of Education; Assessment and Testing; Higher Education; Education Economics; Education Policy